Toxicity Effect of Silver Nanoparticles in Brine Shrimp Artemia - Chinnasamy Arulvasu; Samou Michael Jennifer; Durai Prabhu; Devakumar Chandhirasekar (The Scientific World Journal)
The present study revealed the toxic effect of silver nanoparticles (AgNPs) in Artemia nauplii and evaluated the mortality rate, hatching percentage, and genotoxic effect in Artemia nauplii/cysts. The AgNPs were commercially purchased and characterized using field emission scanning electron microscope with energy dispersive X-ray spectroscopy. Nanoparticles were spherical in nature and with size range of 30–40 nm. Artemia cysts were collected from salt pan, processed, and hatched in sea water. Artemia nauplii (II instar) were treated using silver nanoparticles of various nanomolar concentrations and LC50 value (10 nM) and mortality rate (24 and 48 hours) was evaluated. Hatching percentage of decapsulated cysts treated with AgNPs was examined. Aggregation of AgNPs in the gut region of nauplii was studied using phase contrast microscope and apoptotic cells in nauplii stained with acridine orange were observed using fluorescence microscope. DNA damage of single cell of nauplii was determined by comet assay. This study showed that as the concentration of AgNPs increased, the mortality rate, aggregation in gut region, apoptotic cells, and DNA damage increased in nauplii, whereas the percentage of hatching in Artemia cysts decreased. Thus this study revealed that the nanomolar concentrations of AgNPs have toxic effect on both Artemia nauplii and cysts.